Pengaruh Kualitas Layanan terhadap Kepuasan Pengunjung pada Wisata X Teros di Desa Sapit - Zainul Abidin; Amrullah; Jamaluddin (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the effect of the service quality dimensions of tangibles, reliability, responsiveness, assurance, and empathy on visitor satisfaction at X Teros Tourism in Sapit Village, East Lombok Regency. A quantitative approach with an explanatory research design was employed. Data were collected through questionnaires distributed to 102 respondents selected using purposive sampling. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with SmartPLS 4 software. The findings indicate that the proposed model has strong predictive power, with a coefficient of determination (R²) of 0.810. Hypothesis testing reveals that empathy has a positive and significant effect on visitor satisfaction, with a path coefficient of 0.543 (t = 3.904; p < 0.001), while assurance also has a positive and significant effect, with a coefficient of 0.306 (t = 2.295; p = 0.022). In contrast, the dimensions of tangibles, reliability, and responsiveness do not significantly influence visitor satisfaction. These findings suggest that personal attention, care, trust, and the ability of tourism managers to create a sense of security are the primary determinants of visitor satisfaction in community-based tourism destinations. The study reinforces the applicability of the Expectancy Disconfirmation Theory and the SERVQUAL model in the context of rural tourism while providing practical implications for destination managers to prioritize interpersonal service quality alongside physical facilities. Furthermore, the findings contribute to the development of tourism management literature and provide evidence-based recommendations for improving visitor satisfaction and supporting the sustainable development of community-based tourism destinations.